2010
DOI: 10.1016/j.neuroimage.2010.06.053
|View full text |Cite
|
Sign up to set email alerts
|

The state of tranquility: Subjective perception is shaped by contextual modulation of auditory connectivity

Abstract: In this study, we investigated brain mechanisms for the generation of subjective experience from objective sensory inputs. Our experimental construct was subjective tranquility. Tranquility is a mental state more likely to occur in the presence of objective sensory inputs that arise from natural features in the environment. We used functional magnetic resonance imaging to examine the neural response to scenes that were visually distinct (beach images vs. freeway images) and experienced as tranquil (beach) or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 41 publications
3
63
1
2
Order By: Relevance
“…These are precisely the features that characterise natural surroundings. Earlier studies have shown a link between natural surroundings and the reduction of stress (Ulrich et al, 1991), recovery from surgical interventions (Ulrich, 1984), pain relief (Lechtzin et al, 2010) and enhanced neural connections in the medial prefrontal cortex of the brain (Hunter et al, 2010). This study has shown the percentage stating they are more relaxed after visiting the green space is closely associated with perceived tranquillity.…”
Section: Predicted Ratings and Adjustmentsmentioning
confidence: 59%
“…These are precisely the features that characterise natural surroundings. Earlier studies have shown a link between natural surroundings and the reduction of stress (Ulrich et al, 1991), recovery from surgical interventions (Ulrich, 1984), pain relief (Lechtzin et al, 2010) and enhanced neural connections in the medial prefrontal cortex of the brain (Hunter et al, 2010). This study has shown the percentage stating they are more relaxed after visiting the green space is closely associated with perceived tranquillity.…”
Section: Predicted Ratings and Adjustmentsmentioning
confidence: 59%
“…The medial frontal cortex is part of the extended circuits with functional connectivity to the posterior temporal sulcus, the temporoparietal junction, the anterior temporal cortex, and the basal ganglia and thalamus (Seitz et al, 2011) entertaining a prominent development from adolescence to adulthood (Burnett and Blakemore , 2009 ). Therefore, the frontal cortex provides a top-down modulation of sensory cortices (Gazzaley et al , 2005 ;Hunter et al , 2010 ), which is functionally abnormal in patients with schizophrenia (Bassett and Bullmore , 2009 ) and severely disrupted in the chronic vegetative state (Boly et al , 2011 ). Thus, many components of the brain structures relevant for belief processes have recently been identifi ed.…”
Section: Neurophysiological Basis Of Belief Processesmentioning
confidence: 99%
“…Moreover, the concept of tranquility has been studied in various research areas closely related to soundscape. For instance, a direct brain response with relation to perceived tranquility was measured with neural imaging [12]. Additionally, the tranquility of natural places has been investigated and evaluated with established soundscape indicators [13].…”
Section: Introductionmentioning
confidence: 99%